Complete guide to TRX suspension training : the best exercises and most effective workouts - Dawes, Jay, ....- (Champaign : Human Kinetics, 2017)
For strength, stability, core power, flexibility, and balance, Suspension Training® delivers results. Used by the best of the best, from professional trainers to the elite athletes they work with, Suspension Training is a respected and essential component of conditioning programs worldwide. Now, the ultimate Suspension Training expert shares the ultimate in Suspension Training exercises and programs. Complete Guide to TRX® Suspension Training®, from renowned strength and conditioning expert Dr. Jay Dawes, is the authoritative guide to Suspension Training. This resource is so thorough that it has earned the endorsement of TRX®. Look inside at the instruction, advice, and insights, and you'll see why. This is a one-of-a-kind resource designed to take workouts to unprecedented levels. Complete Guide to TRX® Suspension Training® includes instructions for more than 115 exercises. Complete with photo sequences, variations, and safety recommendations, you'll learn how to develop and integrate strength, power, core stability, flexibility, and balance with the use of a Suspension Trainer ™. In the gym, at home, or on the road, this guide is the ultimate training companion. With over thirty ready-to-use programs, you have options for any situation and every desire. It's all here.
Keywords: Krachttraining